Novel Compound Heterozygous Variants in ZNF526 Causing Dentici‐Novelli Neurodevelopmental Syndrome: A Case Report and Literature Review - Shaoxin Li; Hui Fang; Hong Li; Min Peng; Jinsong Bao; Yunfei Cai; Jing Chen; Zhige Li (Molecular Genetics & Genomic Medicine)
ABSTRACT Background The ZNF526 gene encodes a ubiquitously expressed Kruppel‐type zinc finger protein crucial in transcriptional regulation. Recent studies suggest that biallelic pathogenic variants in ZNF526 may lead to Dentici‐Novelli neurodevelopmental syndrome, characterized by microcephaly, developmental delay, epilepsy, and ocular anomalies. To date, phenotypic details have been reported for only six patients with ZNF526 variants. Methods This study gathered clinical information and genetic data from a child with neurodevelopmental disorders. A three‐dimensional protein model was employed to predict variant effects on protein structure. A literature review was conducted to compare this case with previously reported cases, analyzing clinical features and genetic findings. Results The proband, a 7‐month‐old girl, exhibited developmental delay, microcephaly, limb hypotonia, abnormal brain imaging, and seizures. Chromosomal karyotype analysis and copy number variation analyses were normal. Whole exome sequencing revealed two heterozygous variants in the ZNF526 gene (NM_133444.3): c.1426del (p.Val476Phefs*9), a de novo frameshift variant, and c.1513T;> C (p.Cys505Arg), inherited from her mother. These previously unreported variants are on separate alleles, forming a compound heterozygous state correlated with the clinical presentation. Ocular anomalies were absent, while café‐au‐lait spots may represent a novel feature. Among 12 cases of Dentici‐Novelli neurodevelopmental syndrome, 11 unique ZNF526 variants have been identified, with loss‐of‐function variants possibly linked to seizures. Conclusion This study describes the youngest patient with Dentici‐Novelli neurodevelopmental syndrome, broadening the ZNF526 mutation spectrum and detailing the associated clinical profile. These findings are valuable for genetic diagnosis and family counseling in cases of this syndrome.